English-Latvian Dictionaries in the Age of Electronic Lexicography - Laura Karpinska (Baltic Journal of English Language, Literature and Culture)
In the 21st century the advantages of electronic dictionaries have been widely acknowledged. Electronic dictionaries form an important branch of contemporary lexicography, however, in general English-Latvian lexicography print dictionaries still outnumber the electronic ones since there is only one large English-Latvian dictionary with complex microstructure and two differing user interfaces that is available in the electronic medium. The aim of the study is to analyse the major general English-Latvian electronic dictionary, determine its type and assess the compliance of this dictionary with the standards of contemporary electronic lexicography. The analysis focuses on the evaluation of dictionary microstructure, the accessibility of information, the adaptability of user interface, the use of dictionary-internal and external links and the sources of lexicographical data in the general English-Latvian electronic dictionary. The analysis reveals that even though the microstructure of the electronic dictionary is essentially based on a print dictionary, it has been supplemented by information from various other sources. The dictionary applies some innovative features of contemporary electronic lexicography, but various improvements related to the presentation of some metalinguistic elements, unity of microstructure, diversity of search options, use of dictionary-internal and external links, application of corpus data and multimodality would be necessary to enhance its correspondence to the standards of contemporary electronic lexicography.